(untitled) (Research, Society and Development, 2022)
Goiatuba is a Brazilian municipality, located in the state of Goiás, in the central and western part of the country. The Brazilian Institute of Geography and Statistics (IBGE) estimates that the region belongs to the Meia Ponte micro-region, with a population of 34,307 inhabitants in 2021. Goiatuba a city becomes a hub of a micro-region, with this it begins to attract people from cities and regions neighbors in search of the opportunity to become professional, because the municipality has a teaching unit UNICERRADO at the university center of Goiatuba. The research will address student movements at a regional and local level, analyzing the paths in which they are submitted. Urban mobility refers to the conditions of vehicular displacement and people in the territory in search of goods and services that generate opportunities, qualifications and work. The study aims to show the importance of the quality of urban mobility at the local and regional level, in order to minimize impacts arising from the traffic flow of UNICERRADO students. As can be seen, urban traffic does not cover only at the local city level, but at the regional level, including urban agglomerations and micro-regions. We have seen that student migrations and commuting are far beyond the act of coming and going of students, they are movements that allow different people an aspect of better quality of life, through study.